Literature Review of Improving Working Environment Through Servant Leadership Principles to Reduce Employee Turnover: A Case Study of PT Windblow - Maya Sonia (Eduvest - Journal of Universal Studies, 2025)
Employee turnover remains a critical challenge for organizations, particularly in the healthcare sector, where service quality is directly linked to workforce stability. This study examines the role of servant leadership in fostering a supportive work environment to mitigate employee turnover at PT Windblow, a Sleep & Respiratory Care service provider in Indonesia. Through a combination of secondary data analysis and exit interviews, key factors influencing turnover were identified, including leadership effectiveness and workplace culture. The research highlights how servant leadership principles, such as employee empowerment, ethical behaviour, and professional development, contribute to enhanced job satisfaction, engagement, and retention. By implementing structured leadership interventions and workplace improvements, organizations can create a sustainable work environment that not only reduces turnover but also improves overall performance. This study contributes to the growing body of knowledge on leadership strategies in healthcare services and underscores the importance of people-centric leadership for long-term organizational success.